The Role of Information Systems in the Process of Administrative Decision Making among those who work at the Human Resources Department of the Government of Fujairah - United Arab Emirates - Saleh, Firas Mahdi; Hammoudi, Sondos Abdel Aziz (Arab Journal for Sciences and Research Publishing, 2016)
The current research aimed at identifying the level of relationship between information technology, and making administrative decisions among those who work at the Human Resources Department at Emirate of Fujairah. Therefore, the society of the current research is all the people who work at the department of Human Resources at Emirate of Fujairah from both gender (males and females) with their multi-level jobs. Their number is (86) and (60) of them are taken as a sample which represent (71) of the total research society. To collect data, the researcher used a questionnaire as an instrument for his research. The researcher prepared it and wrote its items which contained (109) items distributed on (4) sides which are: quality of information technology, information quality, service quality, information technology (Software – Hardware). According to the previous findings, the researcher observes that the following results: There is a significantly high relationship between information systems and making administrative decisions at the Human Resources Department. There is a significantly high relationship between system quality, service quality, information quality, Information technology and making administrative decisions.